Delayed eye and other consequences from exposure to methyl isocyanate: 93% follow up of exposed and unexposed cohorts in Bhopal. Issue 8 (August 1990) - Andersson, N; Ajwani, M K; Mahashabde, S; Tiwari, M K; Muir, M K; Mehra, V; Ashiru, K; Mackenzie, C D
Abstract : A follow up study three years after exposure to methyl isocyanate in 93% of exposed survivors and "control" residents in 10 Bhopali communities showed an excess of eye irritation, eyelid infection, cataract, and a decrease in visual acuity among the exposed people. Breathlessness was twice as common in the heavily exposed clusters as those with lower exposure, a trend that could not be explained by different age or smoking patterns (OR 2.05, 95% CI 1.36-3.08). Case referent analysis of outpatient attendances at Bhopal Eye Hospital, considering patients with severe refractive errors and astigmatism as "controls, " showed a 40% increased risk of trachoma, 36% increased risk of other lid infections, and 45% increased risk of irritant symptoms among previously exposed people. "Bhopal eye syndrome" may thus include full resolution of the initial interpalpebral superficial erosion, a subsequent increased risk of eye infections, hyperresponsive phenomena (irritation, watering, and phlyctens), and possibly cataracts. It remains to be confirmed whether this reflects a more generalised disease as a consequence of previous exposure to methyl isocyanate or whether it is only the eye that is affected.